Dinamika Hukum Perlindungan Anak Luar Nikah di Indonesia - Rahajaan, Jakobus Anakletus; Niapele, Sarifa (Public Policy, 2021)
This research emerged from ideas and ideas that started from our concern and empathy with children out of wedlock who all their lives carry a heavy psychological burden, namely stigmatization as adulterous children, illegitimate children and do not get legal protection at all for their rights as a human child. . This study aims to analyze the dynamics of legal protection for children out of wedlock. We use a normative juridical research method, with a statute approach, regarding the problems we present. The results of our research show that, during the period of 76 years of Indonesia's independence, the State (Government)'s concern for children out of wedlock is very less. It is proven by various laws and regulations that absolutely do not provide certainty, justice and legal benefits for children out of wedlock as the rights of a human child. This practice is not in accordance with the principle of a rule of law based on Pancasila and the principle of equality before the law. But then a legal breakthrough emerged which in our opinion is very advanced and phenomenal (extraordinary), namely, the decision of the Constitutional Court (MK) No. 46/PUU-VIII/2010 which gives status, position and rights as legitimate children to children out of wedlock. This legal breakthrough should be appreciated as a spectacular step to make the law a social engineering tool to break down misconceptions about children out of wedlock. however, it is ironic when the things that are missed by children born out of wedlock are rejected by some groups (conservative groups) who oppose the Constitutional Court's decision. So that until now it is still a polemic in society that has not been resolved. Therefore, through a normative juridical analysis, our research tries to provide a solution that the Constitutional Court's decision is very appropriate because it is in accordance with the values ​​of human rights, Pancasila and the principle of Equality before the Law from the State of Law which must provide certainty, justice and justice. benefits of law to every citizen without indiscriminate or discrimination. Conservatives worry that the Constitutional Court's decision can be a way to legitimize adultery, is a worry that is too naive and shallow. In fact, the Constitutional Court's decision can have a domino effect for children out of wedlock, adulterers, and the community. It is time for the dynamics of the law to develop so, where the law is expected to be a tool of social engineering that will change the paradigm and treatment of society towards children out of wedlock. Keywords: Dynamics, Legal Protection, Children Out of Wedlock